(untitled) (Bangladesh Critical Care Journal, 2024)
Background: Determination of intravascular volume status can sometimes be challenging part of critically ill patient’s management in ICU. Invasive haemodynamic monitoring of central venous pressure is a useful guide in directing early resuscitative efforts and assist in reducing the morbidity and mortality of ICU patients with severe sepsis/septic shock. Obtaining invasive hemodynamic monitoring can lead to complications and time consuming. Sonographic measurement of the inferior vena cava (IVC) diameter and IVC collapsibility, termed the caval index is a non-invasive method of estimating the fluid status in critically ill patients. The study was designed to see the correlation between caval index and central venous pressure (CVP) in non-ventilated critically ill patients. Objectives: The aim of the study was to evaluate the correlation of caval index and central venous pressure in non-ventilated critically ill patients. Methods: It was a hospital based descriptive type of cross-sectional study, carried out in the ICU at the Department of Anaesthesia, Analgesia, Palliative & Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka from the period of May 2017 to October 2018. A total number of 86 patients were enrolled in this study. Study subjects were patients (age >18 years) with critically-ill non-ventilated and whom central venous catheter inserted for CVP monitoring. Central venous pressure was measured first by CVP manometer. Then IVC diameter and caval index were measured with curvilinear probe of the Sonosite ultrasound device. The correlation of CVP and CI was calculated. Statistical analyses of the results were obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences (SPSS-24). Results: In this study, according to CVP 33.7% (29) of patients were hypovolemic with mean (±SD) CVP 5.3±1.2 cm H20, euvolemic were 38.3% (33) with mean (±SD) CVP 10.6±1.7 cm H20 and hypervolemic were 27.9% (24) with mean±SD CVP 16.1±1.5 cm H20. Mean caval index (CI) (%) mean (±SD) was found 57.1±7.23 in hypovolemic patients, 39.5±2.65 in euvolemic & hypervolemic patients. So, the result shows >50 % CI is associated with CVP < 8 mm of Hg and < 50% CI is associated with CVP > 8 mm of Hg. Pearsons correlation coefficient test used to assess the strength and nature of correlation between two variables. There was a statistically significant correlation between the mean CVP and the caval index (p < 0.001). So findings revealed that there is an inverse relationship between the caval index and CVP. Conclusion: The caval index had acceptable correlation with CVP at the level of IVC entry into the right atrium. It was concluded that there is an inverse relationship of CVP with the caval index. Bangladesh Crit Care J March 2024; 12 (1): 29-34